Delayed Diagnosis of Congenital Hypothyroidism in a Child with Trisomy 21 and Biotinidase Deficiency and Successful Use of Levothyroxine Sodium Oral Solution - Matthew M. Feldt (Case Reports in Endocrinology)
Endocrine disorders are more common and appear earlier in people with trisomy 21 (T21) than in the general population, with thyroid dysfunction being the most common, including both congenital and acquired hypothyroidism. The treatment for biotinidase deficiency, a condition that occurs in approximately 1 : 110,000 people, is with biotin (vitamin B7) supplementation. However, biotin can interfere with endocrine laboratory assays and cause falsely low thyroid-stimulating hormone (TSH) and elevated free thyroxine (FT4) levels. This can interfere with the timely diagnosis and subsequent treatment of congenital hypothyroidism (CH). This case report describes an infant with partial biotinidase deficiency that was confirmed on day 10 of life. Routine screening erroneously reported “normal” TSH that caused delayed diagnosis of CH due to interference with the TSH assay from concurrent biotin use. Once the biotin treatment was withheld for 4 days and the thyroid function tests repeated, an elevated TSH became apparent. Treatment with tablet levothyroxine (L-T4) was started and subsequently changed to L-T4 oral solution (Tirosint®-SOL) to overcome treatment administration difficulties encountered with the tablet form. This resulted in improved TSH control due to more accurate and consistent dosing compared with the tablet formulation. This is the first report of the use of L-T4 oral solution in an infant with T21 and biotinidase deficiency.